Syntactic Organization of Beliefs Expressed by the Sentence (Asyndetic Constructions) - Сердега, Руслан Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article describes the syntactic organization of beliefs expressed by the sentence. The syntactic organization of such sentences makes it possible to analyze not only the features of the structure, but also their semantic filling. The main attention is spared those sentences functioning in folk speech in form asyndetic constructions. In the analyzed beliefs is dominated by sentences with different types of predicative parts.